2017
DOI: 10.1377/hlthaff.2017.0708
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Income Countries That Face The Most Rapid Shift In Noncommunicable Disease Burden Are Also The Least Prepared

Abstract: Demographic and epidemiological changes are shifting the disease burden from communicable to noncommunicable diseases in lower-income countries. Within a generation, the share of disease burden attributed to noncommunicable diseases in some poor countries will exceed 80 percent, rivaling that of rich countries, but this burden is likely to affect much younger people in poorer countries. The health systems of lower-income countries are unprepared for this change. We examined the shift to noncommunicable disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
153
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 49 publications
1
153
0
2
Order By: Relevance
“…As a result, NCDs are exerting increasing pressure on health care systems, especially in developing countries, leading to vast inflation in health care expenditures. Problematically, the health systems of the lower‐income countries have been mostly unprepared for this shift, as indicated by the fact that NCDs accounted for over 80% of the disease burden in some poor countries, rivalling that in rich countries . A study in Mongolia revealed that a significant proportion of expenditures for NCDs (69%) was borne by households in the form of out‐of‐pocket payments .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, NCDs are exerting increasing pressure on health care systems, especially in developing countries, leading to vast inflation in health care expenditures. Problematically, the health systems of the lower‐income countries have been mostly unprepared for this shift, as indicated by the fact that NCDs accounted for over 80% of the disease burden in some poor countries, rivalling that in rich countries . A study in Mongolia revealed that a significant proportion of expenditures for NCDs (69%) was borne by households in the form of out‐of‐pocket payments .…”
Section: Introductionmentioning
confidence: 99%
“…Low- and Middle-Income Countries (LMICs) face difficult decisions regarding resource allocation, due to scarce resources and large disease burdens [1,2]. Lack of systematic priority setting can lead to inefficient resource allocation and poor-quality healthcare [3].…”
Section: Introductionmentioning
confidence: 99%
“…A previous multinational study showed higher deaths related to cardiovascular events in low-income countries despite their low-risk burden (Yusuf et al, 2014), suggesting that as epidemiologic transitions progress, cardiovascular events related to obesity will only add to the already stressed health care systems in these countries. Results from the current and other previous studies (Bollyky et al, 2017;Mendis, 2010), provide evidence for governments and policy makers of LMICs, and international organizations to prioritize interventions and policy strategies designed to manage epidemiological and lifestyle transitions.…”
Section: Discussionmentioning
confidence: 73%
“…Our research group has previously reported such epidemiologic transition patterning in the relationships between childhood obesity and household income (Broyles et al, ), physical activity and socioeconomic status (Barreira et al, ), but not for sleep duration and socioeconomic status (Manyanga et al, ). The impact of accelerated epidemiologic transitions for childhood adiposity, and physical activity may be excessively burdensome, especially in LMICs, where infectious and other enteral diseases are still prevalent (Remais, Zeng, Li, Tian, & Engelgau, ), and resources to adequately address the dual burden of both communicable and non‐communicable diseases may be unavailable (Bollyky, Templin, Cohen, & Dieleman, ). A previous multinational study showed higher deaths related to cardiovascular events in low‐income countries despite their low‐risk burden (Yusuf et al, ), suggesting that as epidemiologic transitions progress, cardiovascular events related to obesity will only add to the already stressed health care systems in these countries.…”
Section: Discussionmentioning
confidence: 99%